Salinomycin: A Notch Signaling Antagonist - A Novel Way of Targeting Cancer Stem Cells - Muzlera, Carlos U. (The Meducator, 2013)
Dr. Hassell’s research team aims to investigate the roles of therapeutically-relevant genes or gene signatures in the development of “tumour-initiating cells” or breast cancer stem cells. His research team also explores the effects of antagonistic compounds on certain regulatory receptor pathways using in vitro breast cancer cultures and transgenic mouse models. The following research focuses on validating the inhibitory effects of an anti-breast cancer stem cell agent, salinomycin, on downstream Notch signaling. It suggests the possibility of targeting cancer stem cells, the primary culprit in tumour initiation, chemoresistance, and metastasis, by inhibiting key regulatory pathways - such as Notch signaling - that maintain this “stem-like” population.